Quantitative aspects of digestion in ruminants with special reference to reindeer - Huhtanen, Pekka (nor, 2001)
NOR:n 11. pohjoismainen porotutkijakokous, The 11th Nordic Conference on Reindeer Research Kaamanen, Finland, 18-20 june 2001 v ok